ATP-binding cassette (ABC) transporters in human metabolism and diseases - Stefková, J; Poledne, R; Hubácek, J A (Physiological research, 2004)
The ATP-binding cassette (ABC) superfamily of active transporters involves a large number of functionally diverse transmembrane proteins. They transport a variety of substrates including amino acids, lipids, inorganic ions, peptides, saccharides, metals, drugs, and proteins. The ABC transporters not only move a variety of substrates into and out of the cell, but also are also involved in intracellular compartmental transport. Energy derived from the hydrolysis of ATP is used to transport the substrate across the membrane against a concentration gradient. The typical ABC transporter consists of two transmembrane domains and two nucleotide-binding domains. Defects in 14 of these transporters cause 13 genetic diseases (cystic fibrosis, Stargardt disease, adrenoleukodystrophy, Tangier disease, etc.). Mutations in three genes affect lipid levels expressively. Mutations in ABCA1 cause severe HDL deficiency syndromes called Tangier disease and familial high-density lipoprotein deficiency, which are characterized by a severe deficiency or absence of high-density lipoprotein in the plasma. Two other ABCG transporters, ABCG5 and ABCG8, mutations of which cause sitosterolemia, have been identified. The affected individuals absorb and retain plant sterols, as well as shellfish sterols.
Keywords: Adenosine Triphosphate; Metabolism, Inborn Errors; energetický metabolismus; Lipid Metabolism; ABC transportéry; Energy Metabolism; Hydrolysis; Humans; hydrolýza; ATP-Binding Cassette Transporters; adenosintrifosfát; metabolismus lipidů; vrozené poruchy metabolismu; lidé